Anti-diabetic nutraceutical composition from palm leaf extract. - Mohamed, Suhaila (2010)

(untitled)
A comestible composition with anti-diabetic property which is effective in lowering the blood glucose and help reduce oxidative stress in diabetics and have anti-diabetic properties that protect against diabetic complications, retarding diabetes related organ degeneration and effective to hinder or prevent ailments or conditions resulting from, or exacerbated by, a chronic increase in blood sugar including: tissue degeneration, cardiovascular disease, kidney degeneration, loss of cognitive function, weight loss, visual impairment, and vasomotor symptoms which contains extract from palm leaf.